2022
DOI: 10.1200/jco.21.01861
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Oncogenes Are Associated With Increased Metastatic Capacity and Persistent Disease in Pediatric Thyroid Cancers

Abstract: PURPOSE In 2014, data from a comprehensive multiplatform analysis of 496 adult papillary thyroid cancer samples reported by The Cancer Genome Atlas project suggested that reclassification of thyroid cancer into molecular subtypes, RAS-like and BRAF-like, better reflects clinical behavior than sole reliance on pathologic classification. The aim of this study was to categorize the common oncogenic variants in pediatric differentiated thyroid cancer (DTC) and investigate whether mutation subtype classification co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 21 publications
7
43
0
Order By: Relevance
“…** Analysis of the presence of other oncogenic drivers and gene fusions (e.g. RET/PTC and NTRK-fusions) may be considered in Bethesda 3, 4, or 5 due to the fact of increasing awareness that these are also associated with the presence of PTC ( 39 ). In case a BRAF V600E mutation is found, the risk of the thyroid nodule being malignant is high but needs to be confirmed, for example, by frozen section during thyroid surgery.…”
Section: B2 Risk Of Malignancy In a Thyroid Nodule During Childhoodmentioning
confidence: 99%
“…** Analysis of the presence of other oncogenic drivers and gene fusions (e.g. RET/PTC and NTRK-fusions) may be considered in Bethesda 3, 4, or 5 due to the fact of increasing awareness that these are also associated with the presence of PTC ( 39 ). In case a BRAF V600E mutation is found, the risk of the thyroid nodule being malignant is high but needs to be confirmed, for example, by frozen section during thyroid surgery.…”
Section: B2 Risk Of Malignancy In a Thyroid Nodule During Childhoodmentioning
confidence: 99%
“…Pediatric PTCs are known to be more prone to develop nodal and distant metastases than PTCs in adults. 6 The study by Franco et al 2 investigates differences in metastatic tropism on the basis of their tumor drivers within a pediatric cohort, as compared with adults. Consistent with previous studies, 7 Franco found that pediatric PTCs driven by RET or NTRK fusions more frequently develop nodal metastases than fusion-negative tumors.…”
mentioning
confidence: 99%
“…While it is rare in CYP with DTC to require non-standard therapy, molecular genetic testing is likely to be increasingly used to direct targeted palliative therapies (see Recommendation 57). Future trials can also consider the inclusion of molecular subtypes into risk stratification ( Franco et al 2022 ).…”
Section: Resultsmentioning
confidence: 99%